2004
DOI: 10.1007/s00542-004-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Replication of LIGA structures using microcasting

Abstract: Microcasting with a gold base alloy and an Al-bronze as a replication technique for LIGA structures is shown. A LIGA mold insert for injection molding is used to produce PMMA patterns as lost wax models in the microcasting process. Although there are several steps of replication the accuracy of the process is high and allows the fast manufacturing of middle size batches of microstructured parts. The mechanical properties can be varied within a wide range by choosing different casting alloys or cooling rates. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Another point of interest was the limitation of the process regarding the obtainable aspect ratio in dependency of the mold temperature and the filling pressure (Baumeister et al 2002). The focus was also laid on the reduction of the surface roughness (Baumeister et al 2004b). Further research leads to the development of a special investment for microcasting, which is suitable for base alloys and easily removable from the cast parts Rath et al 2006).…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Another point of interest was the limitation of the process regarding the obtainable aspect ratio in dependency of the mold temperature and the filling pressure (Baumeister et al 2002). The focus was also laid on the reduction of the surface roughness (Baumeister et al 2004b). Further research leads to the development of a special investment for microcasting, which is suitable for base alloys and easily removable from the cast parts Rath et al 2006).…”
Section: State Of the Artmentioning
confidence: 99%
“…The porosity however, affects the surface roughness of the mold and, as a consequence, also of the casting. Additionally, the grain size of the filler material in the investment influences the surface roughness of the mold (Baumeister et al 2004b;Rath et al 2006). Therefore, a new approach was investigated in order to reduce the surface roughness further, namely the casting into mold inserts.…”
Section: State Of the Artmentioning
confidence: 99%
“…The addition of 0.1 mass% Pt and Ir, each, results in grain fining. The investigations given in the present article were performed at tensile specimens which were cast into ceramic muffles at a temperature of 1,000°C and afterwards were slowly cooled to room temperature at ambient air (Baumeister et al 2004(Baumeister et al , 2005.…”
Section: Stabilor-g òmentioning
confidence: 99%
“…Through continuous process improvements it is possible to adapt the technology for precision investment casting of components incorporating microfeatures. Recent studies [7][8][9][10][11] reported that when using accurate threedimensional polymer-based patterns and a fine investment powder, VIC showed real potential for a serial production of metallic microcomponents. In particular, this was achieved by employing microinjection moulding for manufacturing plastic casting patterns.…”
Section: Introductionmentioning
confidence: 99%